The Effect of Extract Bitter Melon and Snakehead Fish on Advanced Glycation End Products - Sari Amalia; MI. Diah Pramudianti; Yuwono Hadisuparto (Indonesian Association of Clinical Pathologist and Medical laboratory, 2021)
Diabetes mellitus type-2 is a transformation of insulin function in peripheral tissues or disorders of pancreatic Î² cells. The combination of glycation and glucose oxidation in type 2 DM patients results in the formation of AGEs which can result in oxidative stress. One of the efforts to reduce oxidative stress is the use of natural ingredients as a source of antioxidants. For example, bitter melon (Momordica Charantia) and snakehead fish (Channa Striata) extracts. The combination of bitter melon and snakehead fish extracts against AGEs levels is still limited and has only been tested on Wistar rats and mice. This study aims to determine how much effect the combination of bitter melon and snakehead fish extracts has on AGEs levels in type-2 DM patients. This study was clinical experimental randomized double blind control trial. The experiment conducted at Purwosari Public Health Center, Surakarta and the examination of AGEs levels was in the Clinical Pathology Laboratory of Dr Moewardi Surakarta from July to August 2020. Comparative analysis if the results were normally distributed, in pairs, numerical data and consists of 2 groups then use the paired sample t-test. The results were significant if p